(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract The research aims to shed light on strategic cohesion and its dimensions represented by (strategic logic, organizational excitement, organizational founding, organizational synergy) and measure its impact on achieving organizational prosperity and its dimensions represented by (intellectual capital, innovation, infrastructure, organizational agility, sustainable competitive advantage). The research problem emerged by raising the main question, which is: Does the management of the researched company realize the importance of practicing strategic cohesion and its role in achieving organizational prosperity? The research was applied in the National Insurance Company, and the research relied on the descriptive analytical approach using the questionnaire as the main tool in collecting its data from the community (64) who are in job positions (general manager, branch manager, department manager, m. department manager, Division official, unit official), and the statistical program (SPSS v.25) was used to calculate (arithmetic mean, standard deviation, coefficient of variation, regression coefficient, AR², t-test, F-test). The research reached a number of results, the most prominent of which were: 1- There is a moderate level of interest from the researched company in strategic cohesion. 2- There is a strong positive effect of strategic cohesion in achieving organizational prosperity.